Study of the energy level-crossings in GaAs/AlxGa1-xAs quantum dots - ElSaid, M (Pergamon-Elsevier Science Ltd, 1996)
The energy spectra of two interacting electrons, confined by a parabolic potential, in a magnetic field applied perpendicular to the plane of the quantum dot are obtained. The electron-electron interaction and the energy level-crossings are discussed. Comparison shows that our calculated spectra of the quantum dot states are in good agreement with those of Wagner et al.
Keywords: nanostructures; semiconductors; electron-electron interactions